The effect of lung-conduction exercise in chronic obstructive pulmonary disease: Randomized, assessor-blind, multicenter pilot trial. Issue 3 (21st January 2022) - Lee, Su Won; Park, Jae Jun; Lyu, Yee Ran; Lee, Eun Jung; Kim, Si Yeon; Kang, Weechang; Son, Ji Woong; Jung, In Chul; Park, Yang Chun
Abstract: Background: Pulmonary rehabilitation (PR) is a management modality that improves the quality of life of patients with chronic obstructive pulmonary disease (COPD); however, PR is not readily accessible. Therefore, we developed lung-conduction exercises (LCE) that can be performed easily without any limitations. The purpose of this randomized, assessor-blind, multicenter pilot trial was to compare the effects of LCE with PR and standard care (SC) in COPD patients. Methods: Twenty-five participants who met the eligibility criteria were randomly allocated to the SC group (only medication, n = 9), LCE group (medication + LCE, 5 times a week, n = 8), or PR group (medication + PR, 5 times a week, n = 8). The 6-minute walk distance (6WMD), pulmonary function test, modified Medical Research Council dyspnea scale, COPD assessment test (CAT), and St. George Respiratory Questionnaire (SGRQ) survey were carried out before starting the trial and after 4 and 8 weeks to determine motor performance, lung function, and dyspnea. Results: After 8 weeks, the pulmonary function test scores were the same. The 6MWD (PR, 28.3 ± 38.5; LCE, 14.5 ± 53.1; SC, 11.5 ± 20.5; P  = .984), modified Medical Research Council dyspnea scale (PR, 0.8 ± 1.0; LCE, 0.8 ± 0.8; SC, 0.3 ± 0.5; P  = .772), CAT (PR, 7.3 ± 6.2; LCE, 4.2 ± 5.2; SC, 1.0 ± 2.2; P  = .232), and SGRQ scores (PR, 11.5 ± 15.4; LCE, 5.5 ± 13.1; SC, 4.8 ± 5.1; P  = .358 [PR vs LCE], P  = .795 [PR vs SC]) had improved in order of PR, LCE, and SC group. Although there were no statistically significant differences in the outcome measures between the groups, there were clinically significant improvements in the CAT and SGRQ scores. Conclusions: In this trial, PR showed more improvement in symptoms and quality of life than SC alone. To seek a more precise use of LCE, further full-sized studies with a long duration and additional outcome measures such as psychological assessment tools and cost-effectiveness ratio should be conducted. Trial registration: KCT0004724.